(untitled) (Al-Academy, 2024)
The research deals with the blockchain technology for developing and securing electronic press publishing operations, achieving cybersecurity to prevent tampering with news and theft, knowing who republished the press or used the existing content using the blockchain method, and protecting the intellectual property of the owners of the original content. The research is classified among descriptive studies that adopt the descriptive analytical survey method, and the study is concerned with the qualitative analysis of current facts related to the research topic, and the research community is represented by sites that rely on blockchain technology, and the research concluded that the new blockchain technology is a broad electronic information or data base based on the use of encryption techniques, and that the blockchain documents all transactions in a chronological sequence that prevents any distortion, manipulation or fraud that may occur in the recorded transactions. Due to the emergence and spread of fabricated or falsified news in journalism, alongside the unauthorized plagiarism of reports and articles violations that infringe upon the moral and financial rights of their original creators, various technologies have been introduced, including blockchain. These technologies have been designed to detect and counter falsification, as well as to safeguard intellectual property rights. As such, they have become a critical necessity for ensuring the protection of rights and the dissemination of truth. Blockchain technology operates through the creation of distributed records across the internet, enabling all participating entities to access a verified copy of the records, documented chronologically. This mechanism effectively prevents tampering, manipulation, or fraud in recorded transactions and ensures attribution to the original publisher, thereby securing their intellectual property rights